Health literacy of primiparae in the first six months of maternity: review - Ivana Olecká; Kateřina Ivanová (Central European Journal of Nursing and Midwifery, 2016)

(untitled)
Aim: The aim of this study was to find out how the health literacy of primiparae in the first six months of motherhood is examined. The following research questions were raised: What methods are used to examine maternal health literacy? What aspects of maternal health literacy are investigated? Do the results prove any link between maternal health literacy and child health? Design: Review. Methods: The search for primary research studies was based on a combination of the following keywords: health literacy, mother*, maternity*, information, and knowledge in the Scopus and Web of Science databases. Exclusion criteria: not a primary study, does not concern research on primiparae of children under six months, unrelated to health literacy research or obtaining of information and acquiring of knowledge, not available in full-text, or clear research methodology description not available. The data were processed using thematic analysis based on the sorting method. Results: 31 studies were found, 17 of which were analysed. The majority of studies used quantitative methods of research with standardized tools. The key categories of health literacy related to obtaining, understanding and use of health information. No direct correlation was clearly demonstrated between level of maternal health literacy and child health. Conclusion: The trend in terms of the focus and goals of professional studies, regardless of cultural or national context, is a shift away from examining the way information is acquired to how it is understood by mothers.